Pengaruh Artificial Intelligence dan Motivasi terhadap Kreativitas Guru Sekolah Dasar Gugus IV Kecamatan Air Sugihan - Gadis Trans Damayanti; Nur Ahyani; Sri Wahyu Indrawati (CV. Ulil Albab Corp, 2026)
This study aims to determine the influence of Artificial Intelligence and motivation on teacher creativity. The research method used a quantitative approach with a multiple linear regression model. Based on the results of statistical analysis using SPSS 26, it was found that the motivation variable obtained an R Square value of 0.420, which means that motivation contributes 42% to teacher creativity, while the remaining percentage is influenced by other variables outside this research. The t- test results show a significance value of 0.000 with a t-count of 6.654 > t-table of 2.00, indicating that motivation has a significant effect on teacher creativity. Likewise, the use of Artificial Intelligence also shows a significant influence and contributes to improving teacher creativity. Simultaneously, both variables are proven to have a significant effect on teacher creativity. Therefore, increasing the use of AI and maintaining high work motivation are important steps in enhancing teacher creativity in the learning process.